Cue-dependent inhibition in posttraumatic stress disorder and attention-deficit/hyperactivity disorder. (October 2017) - Adams, Zachary W.; Meinzer, Michael; Mandel, Howard; Voltin, Joshua; Caughron, Blaine; Sallee, Floyd R.; Hamner, Mark; Wang, Zhewu
Highlights: Response inhibition was compared in 161 adult men with PTSD and/or ADHD and controls. PTSD and ADHD + PTSD were linked to impaired response execution and inhibition. PTSD and ADHD + PTSD showed slower, more variable reaction time relative to controls. No cue dependency differences were observed by PTSD or ADHD diagnosis. Abstract: Objective: Attention-deficit/hyperactivity disorder (ADHD) and posttraumatic stress disorder (PTSD) are common among military veterans, but the comorbidity of these two psychiatric disorders remains largely unstudied. Evaluating response inhibition and cue-dependent learning as behavioral and neurocognitive mechanisms underlying ADHD/PTSD can inform etiological models and development of tailored interventions. Method: A cued go/no-go task evaluated response inhibition in 160 adult males. Participants were recruited from the community and a Veterans Administration medical center. Four diagnostic groups were identified: ADHD-only, PTSD-only, ADHD + PTSD, controls. Results: Group differences were observed across most indices of inhibitory functioning, reaction time, and reaction time variability, whereby PTSD-only and ADHD + PTSD participants demonstrated deficits relative to controls. No cue dependency effects were observed. Conclusion: Finding complement prior work on neurocognitive mechanisms underlying ADHD, PTSD, and ADHD + PTSD. Lack of expected group differences for the ADHD-only group may be due to limited power. Additional work is needed to better characterize distinctions among clinical groups, as well as to test effects among women and youth.